Efeitos de distúrbios antrópicos na regeneração de plantas - Silva, Vanessa Mariano da (2020)
Human disturbances like habitat fragmentation, edge effects, biological invasions, selective logging and grazing often alter biotic and abiotic conditions, potentially affecting plant regeneration. However, there was no research synthesis evaluating how human disturbances affect germination and seedling survival and there is also scarce information about disturbance effects on plant regeneration in biomes such as the Atlantic Forest. We performed two global meta-analyses to evaluate human disturbance effects on seed germination and seedling survival and the influence of disturbance type, vegetation, species traits and phylogeny on species responses to disturbance. In addition, we conducted field experiments to compare microhabitat conditions, seed germination and seed removal of native plant species in the interior and edges of small Atlantic Forest fragments and areas under ecological restoration. Our results indicate an overall negative effect of human disturbance on seed germination, and biological invasion had the largest negative impact. Germination in savannas, shrublands and grasslands was negatively affected by disturbed conditions, as well as seedling emergence of non-tree species. On the other hand, human disturbance did not have a consistent effect on germination of forest species and trees. Dispersal syndrome and seed mass had no effect on species responses. According to our meta-analysis about seedling survival, species responses were highly heterogeneous and human disturbances had no overall effect on seedling survival. The variation in effect sizes was not related to any of the species traits, habitat characteristics or their interactions. Phylogenetic relationships between species did not bias the results in any of our meta-analysis. Our field experiments in an Atlantic Forest landscape in southeastern Brazil indicated that canopy cover and soil moisture differed among the interior of small forest fragments, edges, and restoration areas, with the latter presenting the lowest mean values. Seed germination rates were extremely low in all habitat types for all 13 species studied. Seed removal rates were over 45% of all added seeds and varied according to species and vertebrate exclusion treatment. Our main results suggest that human disturbances generally decrease seed germination, and non-trees from open physiognomies are probably the most susceptible group. Seedling survival responses to disturbance were hard to predict using niche-based approaches, indicating that stochasticity and variability at a microhabitat scale might be important sources of heterogeneity on seedling responses. Our field experiments corroborated the variation of abiotic conditions at a microhabitat scale and the constraints to seedling emergence and recruitment at small fragments and restoration areas. Therefore, conservation practices or restoration efforts focusing on early recruitment, such as direct sowing of seeds, should consider the amelioration of disturbed conditions to enhance the success of those initiatives.